Regular Meals at School as a Factor of Physical Development of Children and Adolescents: Results of a Cohort Study - Igor J. Esaulenko; Tatiana L. Nastausheva; Olga A. Zhdanova; Olga V. Minakova; Iya I. Logvinova; Ludmila I. Ippolitova ("Paediatrician" Publishers LLC, 2016)
Background: In Russian schools, children are provided with meals, and certain categories of students get free meals. However, not all school students eat regularly.Objective: Our aim was to study the role of school meals in physical development of children and adolescents.Methods: The survey of schoolchildren aged 8-18 years (Voronezh) revealed two groups of students who eat at school regularly (Group 1) and on occasions (Group 2). We calculated Z scores of body length and body mass index (BMI) using ANTHROPlus software. Nutritional status was determined based on the values of standard BMI deviations ( +2, +2 to +1, -1 to -2, -2). Health groups were formed according to the Children Health Comprehensive Assessment Instruction.Results: 484 schoolchildren (students of grades 3-11) were examined. 251 (52%) school students had regular meals at school. Regular meal frequency decreased from 69% in the group of 8-10 year old students to 30% in the group of 15-18-year-olds. Z scores of body length in students of Groups 1 and 2 did not differ (0.44 ± 1.00 and 0.30 ± 1.00, respectively; p = 0.124). At the same time, children in Group 1 had higher Z scores of BMI (0.44 ± 1.30 and 0.12 ± 1.30, respectively; p = 0.007). In Group 1, the incidence of overweight and obesity decreased from 40% in group of 8-10 year old students to 15% in 15-18-year-olds, in Group 2 - from 35 to 18%, respectively; incidence of malnutrition increased from 9 to 24% in Group 1 and from 11 to 15% in Group 2. In Group 1, the number of students with health group III or IV was smaller (30% compared to 42% in the control group; p = 0.005).Conclusion: Regular meals at school are an important, but not critical factor in the physical development of children. The absence of regular meals at school may be a risk factor for chronic diseases in schoolchildren.